Impact of solvent polarity on the ligand configuration in tetravalent Thorium N-donor complexes - Sittel, Thomas; Trumm, Michael; Adam, Christian; Geist, Andreas; Panak, Petra (Inorganic chemistry, 2021)
A combined NMR spectroscopic and theoretical study on the complexation of diamagnetic Th(IV) with 2,6-bis(5,6-dipropyl-1,2,4-triazin-3-yl)pyridine (nPr-BTP) was performed. Different ligand configurations were observed for [Th(nPr-BTP)3]4+ complexes depending on the solvent’s ability to actively form hydrogen bonds. In polar aprotic solvents, a complex is observed, which is isostructural with [M(nPr-BTP)3]3+ (M = Am, Ln) complexes studied earlier. In contrast, 1H, 13C, and 15N NMR spectra recorded in polar protic solvents showed twice as many signals, indicating a breakdown of symmetry. Supported by density functional theory (DFT) calculations, this difference is explained by the solvent effect on the steric arrangement of the propyl moieties located on the triazine rings. Important information on bonding properties was obtained by 15N NMR. In contrast to the respective Am(III) complex showing a significant covalent contribution, the Th(IV)-BTP interaction is mainly electrostatic.